(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes effective methods of teaching chemistry in general secondary schools, their alignment with modern educational requirements, and the development of students’ research-based and scientific thinking. In addition to traditional lesson formats, the advantages of interactive and innovative teaching methods – such as experiment-based learning, problem-based learning, the STEM approach, and the use of digital tools–are discussed. The article also presents analytical views on modern forms of assessment and the methodological importance of laboratory work. Based on a review of scientific and pedagogical literature, methodological recommendations aimed at improving the effectiveness of chemistry education have been developed.